HRM 4.0 for human-centered organizations - Bissola, Rita; Imperatori, Barbara (Advanced series in management (Unnumbered), 2019)
This volume of Advanced Series in Management offers cutting-edge research from Human Resource Management professionals and academics, which engages with the potential opportunities and challenges of digitization in the workplace. Contributors introduce fresh evidence and innovative ideas on the changing work environment, to help business leaders' shift to the digital mind-set. The book suggests new ways of managing, organizing, and leading a positive social change towards a human-centered organization. For example, a collaboration between HRM and IT, adoption of design thinking, using integrated analytics, and developing new competences. The book explores this new world for HRM, developing critical insights about three main issues: HRM's new role in the 4.0 era New job and organization design for the smart economy New HRM tools and practices for digital organizations. HRM 4.0 For Human-Centered Organizations provides both researchers and professionals working in Human Resources Management, Organization Design and Organizational Behaviour with practical guidelines to turn the challenging scenario of Industry 4.0 into a successful transformation for the HRM domain.